Respuesta :
Answer:
Step-by-step explanation:
Point slope form: y - y1 = m(x -x1)
[tex]y - [-16] = \dfrac{1}{2}(x - [-3] )\\\\y + 16 = \dfrac{1}{2}(x + 3)\\\\\\y + 16 = \dfrac{1}{2}x + \dfrac{3}{2}\\\\y =\dfrac{1}{2}x+\dfrac{3}{2}-16\\\\y=\dfrac{1}{2}x +\dfrac{3}{2}-\dfrac{32}{2}\\\\\\y=\dfrac{1}{2}x - \dfrac{29}{2}[/tex]
Answer:
[tex]y= -\frac12 x +\frac{29}2[/tex]
Step-by-step explanation:
Let's start with the point- slope form:
[tex]y-y_0=m(x-x_0)[/tex]
and replace the values we have
[tex]y-(-16) = -\frac12 (x-(-3))[/tex]
We're almost there, we just need to write it in a better looking form.
[tex]y+16= -\frac12 (x+3)\\y=-\frac12 x - \frac32 + \frac{32}2\\y= -\frac12 x +\frac{29}2[/tex]